Impact of screening and relaxation on weakly coupled two-dimensional heterostructures - Nguyen, T. T. Nhung; Sollfrank, T.; Tegenkamp, C.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Potassium titanyl phosphate Z- and Y-cut surfaces from density-functional theory - Neufeld, Sergej; Bocchini, Adriana; Schmidt, Wolf Gero (Physical Review Materials)

Surface localized phonon modes at the Si(553)-Au nanowire system - Plaickner, Julian; Speiser, Eugen; Braun, Christian; Schmidt, Wolf Gero; Esser, Norbert; Sanna, Simone (Physical Review B)

GaInP/AlInP(001) Interfaces from Density Functional Theory - Meier, Lukas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

InP and AlInP(001)(2 × 4) Surface Oxidation from Density Functional Theory - Ruiz Alvarado, Isaac Azahel; Karmo, Marsel; Runge, Erich; Schmidt, Wolf Gero (ACS Omega)

Controlled growth of ordered monolayers of N-heterocyclic carbenes on silicon - Franz, Martin; Chandola, Sandhya; Koy, Maximilian; Zielinski, Robert; Aldahhak, Hazem; Das, Mowpriya; Freitag, Matthias; Gerstmann, Uwe; Liebig, Denise; Hoffmann, Adrian Karl; Rosin, Maximilian; Schmidt, Wolf Gero; et al. (Nature Chemistry)

Polaronic enhancement of second-harmonic generation in lithium niobate - Kozub, Agnieszka L.; Schindlmayr, Arno; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)
Density-functional theory within a Berry-phase formulation of the dynamical polarization is used to determine the second-order susceptibility χ(2) of lithium niobate (LiNbO3). Defect trapped polarons and bipolarons are found to strongly enhance the nonlinear susceptibility of the material, in particular if localized at NbV–VLi defect pairs. This is essentially a consequence of the polaronic excitation resulting in relaxation-induced gap states. The occupation of these levels leads to strongly enhanced χ(2) coefficients and allows for the spatial and transient modification of the second-harmonic generation of macroscopic samples.

Band Alignment at Ga x In 1– x P/Al y In 1– y P Alloy Interfaces from Hybrid Density Functional Theory Calculations - Meier, Lukas; Braun, Christian; Hannappel, Thomas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Vibrational Raman spectroscopy on adsorbate-induced low-dimensional surface structures - Speiser, Eugen; Esser, Norbert; Halbig, Benedikt; Geurts, Jean; Schmidt, Wolf Gero; Sanna, Simone (Surface Science Reports)

Free and defect-bound (bi)polarons in LiNbO3: Atomic structure and spectroscopic signatures from ab initio calculations - Schmidt, Falko; Kozub, Agnieszka L.; Biktagirov, Timur; Eigner, Christof; Silberhorn, Christine; Schindlmayr, Arno; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)
Polarons in dielectric crystals play a crucial role for applications in integrated electronics and optoelectronics. In this work, we use density-functional theory and Green's function methods to explore the microscopic structure and spectroscopic signatures of electron polarons in lithium niobate (LiNbO3). Total-energy calculations and the comparison of calculated electron paramagnetic resonance data with available measurements reveal the formation of bound polarons at Nb_Li antisite defects with a quasi-Jahn-Teller distorted, tilted configuration. The defect-formation energies further indicate that (bi)polarons may form not only at Nb_Li antisites but also at structures where the antisite Nb atom moves into a neighboring empty oxygen octahedron. Based on these structure models, and on the calculated charge-transition levels and potential-energy barriers, we propose two mechanisms for the optical and thermal splitting of bipolarons, which provide a natural explanation for the reported two-path recombination of bipolarons. Optical-response calculations based on the Bethe-Salpeter equation, in combination with available experimental data and new measurements of the optical absorption spectrum, further corroborate the geometries proposed here for free and defect-bound (bi)polarons.